Behavioral activation for smoking cessation and mood management following a cardiac event: results of a pilot randomized controlled trial - Andrew M. Busch; Erin M. Tooley; Shira Dunsiger; Elizabeth A. Chattillion; John Fani Srour; Sherry L. Pagoto; Christopher W. Kahler; Belinda Borrelli (BMC, 2017)
Abstract Background Smoking cessation following hospitalization for Acute Coronary Syndrome (ACS) significantly reduces subsequent mortality. Depressed mood is a major barrier to cessation post-ACS. Although existing counseling treatments address smoking and depression independently in ACS patients, no integrated treatment addresses both. We developed an integrated treatment combining gold standard cessation counseling with behavioral activation-based mood management; Behavioral Activation Treatment for Cardiac Smokers (BAT-CS). The purpose of this pilot randomized controlled trial was to test feasibility, acceptability, and preliminary efficacy of BAT-CS vs. Standard of Care (SC). Methods Participants were recruited during hospitalization for ACS and were randomly assigned to BAT-CS or SC. The nicotine patch was offered in both conditions. Smoking, mood, and stress outcomes were collected at end-of-treatment and 24-week follow-up. Results Fifty-nine participants (28 BAT-CS, 31 SC) were recruited over 42 weeks, and assessment completion was above 80% in both conditions. Treatment acceptability and fidelity were high. At 24 week follow-up adjusted odds ratios favoring BAT-CS were 1.27 (95% CI: 0.41-3.93) for 7-day point prevalence abstinence and 1.27 (95% CI: 0.42-3.82) for continuous abstinence. Time to first smoking lapse was significantly longer in BAT-CS (62.4 vs. 31.8 days, p = 0.03). At 24-weeks, effect sizes for mood and stress outcomes ranged from η2 partial of.07-.11, with significant between treatment effects for positive affect, negative affect, and stress. Conclusions The design of this study proved feasible and acceptable. Results provide preliminary evidence that combining behavioral activation with standard smoking cessation counseling could be efficacious for this high risk population. A larger trial with longer follow-up is warranted. Trial registration NCT01964898 . First received by clinicaltrials.gov October 15, 2013.